Informed consent in refractive surgery: in-person vs telemedicine approach - Schallhorn SC (Dove Medical Press, 2018)
Steven C Schallhorn,1–3 Stephen J Hannan,2 David Teenan,2 Martina Pelouskova,2 Julie M Schallhorn1,4 1Department of Ophthalmology, University of California, San Francisco, CA, USA; 2Optical Express, Glasgow, UK; 3Carl Zeiss Meditec, Dublin, CA, USA; 4F.I. Proctor Foundation, University of California, San Francisco, CA, USA Purpose: The aim of this study was to compare the quality of consent process in refractive surgery between patients who had a preoperative consent discussion with the surgeon using a telemedicine approach and those who had a face-to-face discussion.Methods: Patients treated between January and December 2017 (8,184 laser vision correction [LVC] and 3,754 refractive lens exchange [RLE] patients) that attended day 1 and 1-month postoperative visit were retrospectively reviewed. Preoperative consent preparation included a consultation with an optometrist, observation of an educational video, and written information. Patients then selected either a face-to-face appointment with their surgeon (in-clinic group) or a telemedicine appointment (remote group) for their consent discussion, according to their preference. Patient experience questionnaire and clinical data were included in a multivariate model to explore factors associated with consent quality.Results: Prior to surgery, 80.1% of LVC and 47.9% of RLE patients selected remote consent. Of all LVC patients, 97.5% of in-clinic and 98.3% of remote patients responded that they were adequately consented for surgery (P=0.04). Similar percentages in the RLE group were 97.6% for in-clinic and 97.9% for remote patients (P=0.47). In a multivariate model, the major predictor of patient’s satisfaction with the consent process was postoperative satisfaction with visual acuity, responsible for 80.4% of variance explained by the model. Other significant contributors were postoperative visual phenomena and dry eyes, difficulty with night driving, close-up and distance vision, postoperative uncorrected distance visual acuity, change in corrected distance visual acuity, and satisfaction with the surgeon’s approach. The type of consent (remote or in-clinic) had no impact on patient’s perception of consent quality in the regression model.Conclusion: The majority of patients opted for telemedicine-assisted consent. Those who chose it were equally satisfied as those who had a face-to-face meeting with their surgeon. Dissatisfaction with surgical outcome was the major factor affecting patient’s perception of consent quality, regardless of the method of their consent. Keywords: informed consent, telemedicine, refractive surgery, LASIK, photorefractive keratectomy, refractive lens exchange